Uji Efektivitas Pemberian Fermentasi Air Cucian Beras Terhadap Pertumbuhan Tanaman Caisim (Brassica juncea L) Varietas Tosakan - Moh Atoilah; Hayatul Rahmi; Ani Lestari (Jurnal Ilmiah Wahana Pendidikan, 2021)
The experiments begin at Lebak Sari village of Sukaluyu the East Telukjambe sub-districts of Karawang districts from March 2021 until April 2021. The research method that used in this experiments was the experimental method using singular factor Randomized Block Design (RBD). The factor that would be tested was rice rice cleanse water. The design to be done was 7 level treatments that repeated 4 times. The concentration treatment that done in this experiments were A (0% Rice Cleanse Water Concentration), B (20% Rice Cleanse Water Concentration), C (40% Rice Cleanse water Concentration), D (60% Rice Cleanse Water Concentration), E (80% Rice Cleanse Water Concentration), F (100% Rice Cleanse Water Concentration), G (4 gram NPK Fertilizer as a Comparison). Overall, concentration giving of rice cleanse fermentation water into caisim crop (Brassica juncea L.) not yet could gave better significant growth doesn’t really reach maximum for the caisim was because the contents of nutrition that inside of the rice cleanse fermentation water was classified as low. The other factors of caisim crop was the filed environment throughout the experiments such as soil, temperature and orgsnism of crop pest